STRATEGI MENINGKATKAN MUTU DAN DAYA SAING MADRASAH MELALUI PROGRAM UNGGULAN DI MA NU 01 LIMPUNG - SRIANAH, SRIANAH; HARYATI, TITIK; MIYONO, NOOR (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
Educational institutions have an important role in organizing programs to realize educational goals. This program cannot be separated from the role of the school/madrasah principal as the leader of an educational institution. Each leadership has its own strategy for improving the quality of the institution it leads. Quality and competitiveness are related to each other. MA NU 01 Limpung, which is a science and skills-based madrasah, has two superior programs, namely life skills and volleyball extracurriculars which can improve the quality and competitiveness of the madrasah. This research is descriptive qualitative research. The sampling technique used is a purposive sampling technique. Data collection techniques through interviews, observation and documentation studies. Next, the data is analyzed through data reduction, data presentation, and verification or drawing conclusions. Test the validity of the data using the data triangulation method. The research results prove that MA NU 01 Limpung is synonymous with its life skills program and is an attraction for prospective new students. Meanwhile, extracurricular volleyball has resulted in championship achievements in every volleyball competition. This shows that the strategy for improving the quality and competitiveness of the MA NU 01 Limpung madrasah against other schools is through superior non-academic programs, namely life skills and volleyball extracurriculars. ABSTRAKLembaga pendidikan mempunyai peran penting dalam menyelenggarakan program untuk mewujudkan tujuan pendidikan. Program tersebut tidak lepas dari peran kepala sekolah/madrasah sebagai pemimpin sebuah lembaga pendidikan. Setiap kepemimpinan mempunyai strategi sendiri dalam meningkatkan mutu lembaga yang dipimpinnya. Mutu dan daya saing saling berkaitan satu sama lain. MA NU 01 Limpung yang merupakan madrasah berbasis keilmuan dan skill mempunyai dua program unggulan yaitu life skill dan ekstrakurikuler bola voli yang dapat meningkatkan mutu dan daya saing madrasah. Penelitian ini merupakan penelitian kualitatif deskriptif. Teknik sampling yang digunakan adalah teknik sampling purposive. Teknik pengumpulan data melalui wawancara, observasi, dan studi dokumentasi. Selanjutnya data dianalisis melalui reduksi data, penyajian data,dan verifikasi atau penarikan kesimpulan. Uji keabsahan data menggunakan metode triangulasi data. Hasil penelitian membuktikan bahwa MA NU 01 Limpung identik dengan program life skill-nya dan menjadi daya tarik bagi calon peserta didik baru. Sedangkan, ekstrakurikuler bola voli telah membuahkan hasil prestasi kejuaraan dalam setiap ajang perlombaan bola voli. Hal tersebut menunjukkan bahwa strategi dalam meningkatkan mutu dan daya saing madrasah MA NU 01 Limpung terhadap sekolah lain adalah melalui program unggulan non akademik yaitu life skill dan ekstrakurikuler bola voli.